THE DEVELOPMENT AND PILOT IMPLEMENTATION OF ELPSA FRAMEWORK FOR LEARNING STATISTICS - Raihan, Raihan; Johar, Rahmah; Munzir, Said (Jurnal Pengajaran MIPA, 2018)
Previous studies suggested that real-world problems and students’ characteristics should be emphasized when designing statistics teaching materials. ELPSA Framework could address those considerations and was used as a learning framework for teaching statistics to junior high school students. Prior to classroom implementation, the teaching materials was tested and deemed valid and practical. Pilot implementation results showed that the teaching materials was effective for learning statistics because the ELPSA framework components facilitate students’ understanding of statistical concepts. Students also perceived learning based on the ELPSA framework positively because it enables them to enjoy the learning process.